A partial MECP2 duplication in a mildly affected adult male: a putative role for the 3' untranslated region in the MECP2 duplication phenotype - Hanchard Neil A; Carvalho Claudia MB; Bader Patricia; Thome Aaron; Omo-Griffith Lisa; del Gaudio Daniela; Pehlivan Davut; Fang Ping; Schaaf Christian P; Ramocki Melissa B; Lupski James R; Cheung Sau Wai (BMC, 2012)
Abstract Background Duplications of the X-linked MECP2 gene are associated with moderate to severe intellectual disability, epilepsy, and neuropsychiatric illness in males, while triplications are associated with a more severe phenotype. Most carrier females show complete skewing of X-inactivation in peripheral blood and an apparent susceptibility to specific personality traits or neuropsychiatric symptoms. Methods We describe the clinical phenotype of a pedigree segregating a duplication of MECP2 found on clinical array comparative genomic hybridization. The position, size, and extent of the duplication were delineated in peripheral blood samples from affected individuals using multiplex ligation-dependent probe amplification and fluorescence in situ hybridization, as well as targeted high-resolution oligonucleotide microarray analysis and long-range PCR. The molecular consequences of the rearrangement were studied in lymphoblast cell lines using quantitative real-time PCR, reverse transcriptase PCR, and western blot analysis. Results We observed a partial MECP2 duplication in an adult male with epilepsy and mild neurocognitive impairment who was able to function independently; this phenotype has not previously been reported among males harboring gains in MECP2 copy number. The same duplication was inherited by this individual's daughter who was also affected with neurocognitive impairment and epilepsy and carried an additional copy-number variant. The duplicated segment involved all four exons of MECP2, but excluded almost the entire 3' untranslated region (UTR), and the genomic rearrangement resulted in a MECP2-TEX28 fusion gene mRNA transcript. Increased expression of MECP2 and the resulting fusion gene were both confirmed; however, western blot analysis of lysates from lymphoblast cells demonstrated increased MeCP2 protein without evidence of a stable fusion gene protein product. Conclusion The observations of a mildly affected adult male with a MECP2 duplication and paternal transmission of this duplication are unique among reported cases with a duplication of MECP2. The clinical and molecular findings imply a minimal critical region for the full neurocognitive expression of the MECP2 duplication syndrome, and suggest a role for the 3' UTR in mitigating the severity of the disease phenotype.